Diet and its association with reduced semen quality - Ochyra, Łukasz; Łopuszyńska, Anna; Pawlicki, Mateusz; Piecewicz-Szczęsna, Halina (Journal of Education, Health and Sport, 2022)
Introduction: Infertility is defined as the inability to conceive a child for at least 12 months of regular unprotected intercourse and may affect up to 15% of couples of reproductive age. Reduced semen quality may be caused by trauma, inflammation, or an inappropriate lifestyle. Research suggests that diet may be a factor in influencing sperm parameters. Material and methods: The literature of the PubMed scientific base was searched in 2015-2022 using the following keywords: semen, diet, infertility. Results: Analyzes of eating patterns showed that eating a diet high in red meat, high-fat dairy, sweet energy drinks, and snacks could negatively affect semen, and a pattern based on the consumption of fish, chicken, vegetables, fruits, legumes, and whole grains was associated with with an increased concentration of sperm. A high-fat diet (HFD) leads to obesity, endocrine disorders, dysbiosis of the intestinal microflora, and may be a factor that activates autophagy, which results in reduced sperm quality. A ketogenic diet can positively affect the semen of obese, infertile men. Studies analyzing the Mediterranean diet suggest that higher compliance rates are associated with a higher percentage of mobility as well as a reduced risk of low sperm concentration. The way you prepare your meals can also play a role as glycation end products are produced when grilling, baking and frying, which can damage sperm DNA. Conclusions: Diet may be an important factor influencing the quality of sperm in men, however, there is a need for further extensive, multi-center studies that will systematize this knowledge, which will enable the creation of specific nutritional recommendations for this group of people.